Risk of biochemical recurrence and timing of radiotherapy in pT3a N0 prostate cancer with positive surgical margin: A single center experience Risiko für ein biochemisches Rezidiv und Zeitpunkt der Strahlentherapie bei pT3a N0 Prostatakarzinom mit positivem Schnittrand: Eine monozentrische Analyse - Hegemann, Nina Sophie; Morcinek, Sebastian; Buchner, Alexander; Karl, Alexander; Stief, Christian; Knüchel, Ruth; Corradini, Stefanie; Li, Minglun; Belka, Claus; Ganswindt, Ute (Strahlentherapie und Onkologie, 2016)
Background: Despite improved biochemical recurrence-free survival rates by the use of immediate adjuvant radiotherapy (RT) in patients with locally advanced prostate cancer, disagreement about the need and timing of RT remains. Patients and methods: From 2005–2009, 94 patients presenting with a stage pT3a N0 and microscopic positive resection margin were retrospectively analyzed after radical prostatectomy. Special attention was given to patients’ outcome, the frequency of additive RT, and its efficacy. Results: Median follow-up was 80 months. A total of 71 patients had a negative postoperative prostate-specific antigen (PSA) level (<0.07 ng/ml). Thirty-six of them did not experience any PSA relapse (subgroup 1). Fourteen of them received additive RT and during follow-up all 36 patients remained PSA negative. Of 71 initially PSA-negative patients, 35 had a biochemical relapse (subgroup 2); 28 patients underwent salvage RT. The median PSA value before salvage RT was 0.24 ng/ml and was subsequently negative (<0.07 ng/ml) in 23 patients after RT. Of the entire cohort, 23 patients had persisting PSA after surgery (subgroup 3). Of these, 18 patients received salvage RT at a median PSA level of 0.4 ng/ml. One patient in subgroup 1, 5 patients in subgroup 2, and 9 patients in subgroup 3 had ongoing androgen deprivation therapy. Conclusion: The present study of 94 pT3a N0 R1 prostate cancer patients provides insight into medical care of this patient cohort and underlines the need for additive RT for the majority of patients to achieve long-term biochemical control. Although immediate adjuvant RT was applied with restraint (20 %), during the observation period 60 of 94 patients (63.8 %) received RT – highlighting the need of postoperative treatment.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Biochemical relapse; Postoperative radiotherapy; Prostate cancer; Radical prostatectomy; Salvage radiotherapy